Sub-lethal combined effects of illicit drug and decreased pH on marine mussels: A short-time exposure to crack cocaine in CO2 enrichment scenarios. (October 2021) - da Silva Souza, Lorena; Bonnail, Estefanía; Maranho, Luciane Alves; Pusceddu, Fabio Hermes; Cortez, Fernando Sanzi; Cesar, Augusto; Ribeiro, Daniel Araki; Riba, Inmaculada; de Souza Abessa, Denis M.; DelValls, Ángel; Pereira, Camilo Dias Seabra
Abstract: The increasing CO2 -concentrations in the atmosphere promote ocean acidification. Seawater chemistry changes interact with contaminants, such as illicit drugs in the coastal zones. This work evaluates impacts of pH decrease and crack-cocaine exposure on the commercial mussel Perna perna through biomarker responses (lysosomal membrane stability, lipid peroxidation, and DNA strand breaks). The organisms were exposed to different crack-cocaine concentrations (0.5, 5.0, and 50 μg L −1 ) combined with different pH values (8.3, 8.0, 7.5, 7.0, 6.5, and 6.0) for 96 h. Crack-cocaine in the different acidification scenarios triggered cyto-genotoxicity, which affected the overall health of mussels exposed to cocaine environmentally relevant concentration. This study produced the first data on biomarker responses associated with CO2 -induced acidification and illicit drugs (crack-cocaine) in marine organisms. Graphical abstract: Unlabelled Image Highlights: Ocean acidification scenarios were assessed with mussel in presence of crack-cocaine. Lysosomal membrane stability, lipid peroxidation, and DNA strand breaks in Perna perna revealed toxicity increase. Adverse effects of acidification were detected for pH below 6.5. At pH 7.5–6.5 adverse effects are related to combined stressors (CO2 and cocaine)